Comparison of Measured Neutron Yield Versus Pressure Curves for FMPF-3, NX2 and NX3 Plasma Focus Machines Against Computed Results Using the Lee Model Code - Saw, S. H.; Lee, P.; Rawat, R. S.; Verma, R.; Subedi, D.; Khanal, R.; Gautam, P.; Shrestha, R.; Arwinder, Singh*; Lee, S. (Springer US, 2015)
A range of plasma focus machines from the 200 J FMPF3 through the 2 kJ NX2 to the 20 kJ NX3 are operated at the National Institute of Education in Singapore. The neutron yield Yn versus pressure P curves for these machines have been measured and published. We use the Lee code to compute these Yn versus P curve for each machine after fitting a computed current waveform to a current waveform measured from each machine. Comparison of computed with measured Yn versus P curves show good agreement of peak Yn for the NX2 and NX3 whilst the measured peak Yn of FMPF3 is larger than the computed by a factor of 3. The computed curve is generally broader whilst the NX3 computed curve also shows a shift to higher pressures than the measured curve. The results are critically discussed.